2018
DOI: 10.1111/ajt.14948
|View full text |Cite
|
Sign up to set email alerts
|

De novo or early conversion to everolimus and long-term cancer outcomes in kidney transplant recipients: A trial-based linkage study

Abstract: Choice of immunosuppression may modify the risk of cancer after kidney transplantation, however, long-term data are lacking. Using the Australian and New Zealand Dialysis and Transplant Registry, we compared the 9-year risk of incident cancer, non-melanoma skin cancer (NMSC), and death attributed to cancer among participants from Australia and New Zealand in four randomized-controlled trials which compared de novo or early switch to an everolimus-containing regimen with calcineurin-inhibitor-based triple thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Hence, mTOR inhibitor–based regimens have been used de novo to prevent cancer development in transplant patients with high cancer risk and conversion to an mTOR inhibitor–based regimen is often considered if cancer is diagnosed. Whereas a 2014 meta-analysis showed a decreased risk of malignancy by 40% (driven mainly by the decreased risk of non-melanoma skin cancer) 112 , recent large studies have failed to show a difference in overall malignancy risk between patients on mTOR inhibitor–based immunosuppression and other regimens 113116 . Some studies have not included non-melanoma skin cancer in their analysis, but most of the studies that did have found a decreased risk of non-melanoma skin cancer (particularly basal cell carcinoma) 112, 114, 116119 .…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, mTOR inhibitor–based regimens have been used de novo to prevent cancer development in transplant patients with high cancer risk and conversion to an mTOR inhibitor–based regimen is often considered if cancer is diagnosed. Whereas a 2014 meta-analysis showed a decreased risk of malignancy by 40% (driven mainly by the decreased risk of non-melanoma skin cancer) 112 , recent large studies have failed to show a difference in overall malignancy risk between patients on mTOR inhibitor–based immunosuppression and other regimens 113116 . Some studies have not included non-melanoma skin cancer in their analysis, but most of the studies that did have found a decreased risk of non-melanoma skin cancer (particularly basal cell carcinoma) 112, 114, 116119 .…”
Section: Cancermentioning
confidence: 99%
“…Whereas a 2014 meta-analysis showed a decreased risk of malignancy by 40% (driven mainly by the decreased risk of non-melanoma skin cancer) 112 , recent large studies have failed to show a difference in overall malignancy risk between patients on mTOR inhibitor–based immunosuppression and other regimens 113116 . Some studies have not included non-melanoma skin cancer in their analysis, but most of the studies that did have found a decreased risk of non-melanoma skin cancer (particularly basal cell carcinoma) 112, 114, 116119 . Nonetheless, mTOR inhibitor–based immunosuppression regimens have been associated with increased risk of mortality 112, 115 and post-transplant lymphoproliferative disorder 120, 121 .…”
Section: Cancermentioning
confidence: 99%
“…Recently, the TRANSFORM randomized trial showed that EVR in association with reduced CNI exposure was as effective as the standard CNI‐mycophenolic acid (MPA) regimen for preventing the occurrence of dn DSA and rejection in patients with mild to moderate immunologic risk, 41 with a very good safety profile. Interestingly, the association of mTORi with a low‐dose CNI could be sufficient to reduce cancer frequency 28,42‐44 . Based on these data, we proposed to our KTRs with at least one NMSC a conversion to EVR in association with reduced CNI exposure.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, the impact c o m m e n t a r y Kidney International (2019) 96, 13-30 on longer-term, hard outcomes will be the ultimate determinant of comparative efficacy, given associations between mTORi and increased mortality in registry studies and meta-analyses, yet some evidence that de novo mTORi may afford protection from cancer. 9 Exactly how this data will be obtained remains unclear because the 3 trials discussed were short term only. Linkage to registries 9 or administrative data sets may provide some of the answers.…”
mentioning
confidence: 99%
“…9 Exactly how this data will be obtained remains unclear because the 3 trials discussed were short term only. Linkage to registries 9 or administrative data sets may provide some of the answers. DISCLOSURE SC has received research funding (to institution), travel support, or speakers fees from Novartis, Astellas, Amgen, and Vitaeris.…”
mentioning
confidence: 99%